AN INHOMOGENEOUS MULTI-ATTRIBUTE DECISION MAKING METHOD AND APPLICATION TO IT/IS OUTSOURCING PROVIDER SELECTION - Qiang, Rui; Li, Debiao (International Journal of Industrial Engineering: Theory, Applications and Practice, 2015)
Selecting the suitable outsourcing provider is one of the most critical activities in supply chain management. In this paper, a new fuzzy linear programming method is proposed to select outsourcing providers by formulating it as a fuzzy inhomogeneous multi-attribute decision making (MADM) problems with fuzzy truth degrees and incomplete weight information. In this method, the decision maker’s preferences are represented as trapezoidal fuzzy numbers (TrFNs), which obtained through pair-wise comparisons of alternatives. Based on the fuzzy positive ideal solution (FPIS) and fuzzy negative ideal solution (FNIS), the fuzzy consistency and inconsistency indices are defined by the relative closeness degrees in TrFNs. The attribute weights are estimated by solving the proposed fuzzy linear programming. And then the selection ranking is determined by the comprehensive relative closeness degree of each alternative to the FPIS. An industrial IT outsourcing provider selection example is analyzed to demonstrate the implementation process of this method.